Taste of modernity : Sufism, Salafiyya, and Arabism in late Ottoman Damascus - Weismann, Itzchak (Leiden ; Boston : Brill, 2001)
Modernization in the Muslim world was determined by the two interrelated processes of indigenous state formation and European economic penetration. This study traces the emergence of modern Islam and examines the relationship of Islamic modernization to the rise of Arab Nationalism.
Acknowledgments; Introduction; Part One: In Support of the Sultan -- The Naqshbandiyya-Khalidiyya; Part Two: Facing the West -- The Akbariyya; Part Three: Resistance to the Emerging Modern State -- The Salafiyya; Conclusion; Select Bibliography; Index.
Includes bibliographical references (pages 317-333) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Salafīyah -- Syria; Sufism -- Syria -- Damascus -- History; Islam -- Syria -- Damascus -- History; Salafiyya -- Syrie; Soufisme -- Syrie -- Damas -- Histoire; Islam -- Syrie -- Damas -- Histoire; RELIGION -- Islam -- History; Islam; Salafīyah; Sufism; Syria; Syria -- Damascus; History